2021
DOI: 10.1098/rspb.2021.0552
|View full text |Cite
|
Sign up to set email alerts
|

Fungal microbiomes are determined by host phylogeny and exhibit widespread associations with the bacterial microbiome

Abstract: Interactions between hosts and their resident microbial communities are a fundamental component of fitness for both agents. Though recent research has highlighted the importance of interactions between animals and their bacterial communities, comparative evidence for fungi is lacking, especially in natural populations. Using data from 49 species, we present novel evidence of strong covariation between fungal and bacterial communities across the host phylogeny, indicative of recruitment by hosts for specific su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…This is consistent with studies on humans and ruminants (Kittelmann et al, 2012; Qin et al, 2010). Similarly, a study looking at a wide range of animal hosts found that Shannon diversity was higher for bacteria than for fungi in 47 out of 49 species (Harrison et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This is consistent with studies on humans and ruminants (Kittelmann et al, 2012; Qin et al, 2010). Similarly, a study looking at a wide range of animal hosts found that Shannon diversity was higher for bacteria than for fungi in 47 out of 49 species (Harrison et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, a frog that is suitable for hosting a rich assemblage of bacteria may also be suitable for hosting a rich assemblage of fungi. Indeed, Harrison et al (2021) found evidence of co‐occurrence between fungi and bacteria and associations between host phylogeny and microbiomes across a range of species, suggesting that aspects of the hosts were simultaneously selecting specific fungi and bacteria. This explanation is reasonable given that, on a particular frog, both communities will be exposed to the same antimicrobial peptides and experience the same environments and climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, bacterial and fungal communities co-varied within all samples and both within and between housefly strains. Co-variation of the bacterial and the fungal microbiota has been reported in the case of many species 47 . A major gap in our knowledge is the extent to which this phenomenon can be attributed to selection by the host or to interactions within the microbiome.…”
Section: Discussionmentioning
confidence: 95%
“…A transfer of microbes across predator-prey networks has been suggested for insectivorous birds and predatory insects ( Tiede et al, 2017 ; Suenami et al, 2019 ; Dion-Phénix et al, 2021 ). The mammalian microbiota is strongly influenced by species identity and type of diet, but an increase of invertebrate prey (i.e., insects) within the diet correlates with a decrease in bacterial alpha diversity compared to mammals with a primarily herbivorous lifestyle ( Knowles et al, 2019 ; Harrison et al, 2021 ). Tough “insectivory” includes the consumption of non-flying insects (i.e., ants or termites) as well as other invertebrates, such a dietary preference seems to result in a convergent adaptation in the microbiota of phylogenetically distant mammalian clades (Pilosa, Cingulata, Tubulidentata, and Carnivora) ( Delsuc et al, 2014 ).…”
Section: How Host Movement Shapes the Host Microbiotamentioning
confidence: 99%